Mali: Agromali - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The website Agromali.com of the Centre Agro-Entreprise (CAE) offers access to market information, publications and training to promote the production, post-harvest and marketing of agricultural products.